Relationship between heart rate recovery and inflammatory markers in patients with polycystic ovary syndrome: a cross-sectional study - Giallauria Francesco; Orio Francesco; Lombardi Gaetano; Colao Annamaria; Vigorito Carlo; Tafuri Maria; Palomba Stefano (BMC, 2009)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine disease closely related to several risk factors for cardiovascular disease. An abnormal heart rate recovery (HRR), an easily-obtained measure derived from exercise stress test and closely related to an increased risk for cardiovascular mortality, has been recently described in PCOS women. A subclinical increase of the inflammation markers has been also observed in the PCOS. This study was designed to study the relationships between HRR and inflammatory markers in PCOS women. Methods Two-hundred forty-three young PCOS patients without known risk factors for cardiovascular risk were enrolled. All patients underwent hormonal and metabolic profile, white blood cells (WBCs) count and C-reactive protein (CRP). HRR was calculated as the difference between heart rate at peak exercise and heart rate at first minute of the cool-down period. Abnormal HRR was defined as ≤18 beats/min for standard exercise testing. Results Eighty-nine out of 243 patients presented abnormal HRR. Serum CRP (1.8 ± 0.7 vs. 1.1 ± 0.4 mg/dl, p < 0.001) and WBCs (7.3 ± 1.8 vs. 6.6 ± 1.5 109 cells/l, p < 0.001) concentrations were significantly higher in PCOS patients with abnormal versus normal HRR. HRR was significantly associated with both CRP (r = -0.33, p < 0.001) and WBCs (r = -0.29, p < 0.001), although in a stepwise multiple regression HRR resulted independently associated with CRP (beta = -0.151, p = 0.001) alone. In a logistic multivariate model, the group within the highest quartile of CRP (odds ratio 1.59, 95% CI 1.07-2.33) was more likely to have abnormal HRR than those within the lowest quartile. Conclusion Abnormal HRR and inflammatory markers are closely associated in PCOS women acting probably in concert to increase the cardiovascular risk profile of these patients.